Coffeeshop Vs Warkop ? - Septa Handika; Karunia Tripuspa; Ervina Dwi; Nadya Safitri; Dilawatur Rohmah; Hanifah (PUTRA JAWA PUBLISHER, 2023)
This article discusses the competition between coffeeshops and warkop in the coffee industry in Indonesia. The purpose of this article is to analyze the differences between the two types of coffee places and how the competition between them occurs. The method used in this article is qualitative research. The results of the study show that coffeeshops emphasize a higher-quality coffee experience and flavor, while warkop offers more affordable prices and a friendlier atmosphere. Competition between the two types of coffee places occurs due to differences in target markets and marketing strategies. Coffeeshops target consumers who are looking for a higher-quality coffee experience and flavor, while warkops target consumers who are looking for a relaxed atmosphere and affordable prices. Both types of coffee places also have their own advantages and disadvantages. Coffeeshops have higher quality coffee flavors but higher prices, while warkops have more affordable prices but lower quality coffee. In conclusion, competition between coffeeshops and warkops in the coffee industry in Indonesia occurs due to differences in target markets and marketing strategies. Both types of coffee places have their own advantages and disadvantages, and consumers can choose according to their preferences.